Seed dissemination by frugivorous birds from forest fragments to adjacent pastures on the western slope of Volcán Barva, Costa Rica - Barrantes Montero, Gilbert (2002)
Logging, cattle raising, and agricultural activities have caused the destruction of most forested áreas in Costa Rica. In some middle and highlands the abrupt topography delayed the complete destruction of montane forest. Consequently, some fragments of almost pristine forest remain along streams that run in deep canyons. Frequently, these remnants serve as corridors between larger forested areas and as routes for movement of frugivorous birds. Eighteen bird species, e.g., Turdus plebejus, Elaenia frantzii and Ptilogonys caudatus are common dwellers of forest patches throughout the Pacific slope of the Volcán Barva. These species fly fre- quently from forest fragments to adjacent pastures. They defecated and regurgitated seeds of 28 plant species on stumps scattered on pasture areas. Isolated trees and specially the stumps are suitable microhabitats for germination of seeds and establishment of seedlings.